A Pediatric Intra-Axial Malignant SMARCB1-Deficient Desmoplastic Tumor Arising in Meningioangiomatosis. Issue 10 (30th August 2018) - Rossi, Sabrina; Brenca, Monica; Zanatta, Lucia; Trincia, Elena; Guerriero, Angela; Pizzato, Cristina; Fiorindi, Alessandro; Viscardi, Elisabetta; Giangaspero, Felice; Maestro, Roberta; Dei Tos, Angelo Paolo; Giannini, Caterina
Abstract: SMARCB1 inactivation is a well-established trigger event in atypical teratoid/rhabdoid tumor. Recently, a role for SMARCB1 inactivation has emerged as a mechanism of clonal evolution in other tumor types, including rare brain tumors. We describe an unusual malignant intra-axial SMARCB1 -deficient spindle cell desmoplastic neoplasm, occurring in a 6-year-old child with meningioangiomatosis and a long history of seizures. Striking features of the tumor were a storiform pattern and strong CD34 expression. Undifferentiated round cell areas with isolated rhabdoid cells showing high mitotic index and focal necrosis with INI1 expression loss were present. The meningioangiomatosis component showed few chromosomal imbalances, including chromosomal 22 monosomy (where SMARCB1 maps) and gain at 6q14.3. In addition to these abnormalities, the spindle cell desmoplastic neoplasm and its dedifferentiated SMARCB1 -deficient component shared several other aberrations, including homozygous deletion at 9p21.3, losses at 1p, 3p, 3q, 10p, and 13q, gains and losses at 5p and 11p. In line with INI1 loss, the dedifferentiated component showed remarkably decreased levels of SMARCB1 transcript. The residual SMARCB1 allele was wildtype. Our findings suggest progression from the meningioangiomatosis to the malignant desmoplastic neoplasm through the occurrence of complex chromosomal abnormalities, and point to functional silencing of SMARCB1 in the dedifferentiation component.